ETHICS WITHIN THE SUNDANESE LOCAL WISDOM “TRISILAS”: A PHILOSOPHICAL STUDY OF MORAL DISENGAGEMENT AMONG STUDENTS: ETIKA DALAM NILAI KEARIFAN LOKAL ”TRISILAS” (SILIH ASIH, ASAH, ASUH): STUDI FILSAFAT TENTANG MORAL DISENGAGEMENT DI KALANGAN SISWA - Nandia Kiranti; Yusuf Tri Herlambang; Dinie Anggraeni Dewi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The development of technology and digital media has influenced the moral behavior of young generations, marked by the increasing phenomenon of moral disengagement such as cyberbullying, lack of empathy, and weak social responsibility among students. This study aims to analyze the Sundanese local wisdom values silih asah, silih asih, and silih asuh (Trisilas) as an ethical foundation for addressing moral disruption among students. The method used is a systematic literature review (SLR) employing the PRISMA approach on 20 scientific articles published between 2020 and 2025. The analysis results indicate that Trisilas values function as a moral and social strengthening mechanism capable of reducing moral disengagement tendencies by fostering empathy, responsibility, and solidarity within educational environments. Silih asah develops intellectual reflection, silih asih cultivates emotional concern, and silih asuh reinforces students’ social responsibility. The integration of these values in modern education aligns with virtue ethics, which emphasizes moral habituation through communal culture. Thus, the internalization of Trisilas local wisdom can serve as an effective strategy to build students’ character and moral awareness in the digital era while simultaneously strengthening the nation’s cultural identity and spirituality in facing global challenges.